Pengaruh Kesesuaian Kompensansi, Pengendalian Internal, Budaya Organisasi dan Kompetensi Akuntansi Terhadap Penyalahgunaan Dana Desa Pada Kantor Desa Kabupaten Gresik - NOVITASARI, DINA DWI; Irma SL, Ade; Anggraini A, Ratna (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to see the effect of compensation suitability, accounting system, internal control, organizational culture and accounting competence, and using the dependent variable, namely the misuse of village funds. The object of the study is the Village Office of Gresik Regency. Data from this study were obtained by distributing questionnaires to 63 respondents through purposive sampling. The data analysis method in this study uses descriptive statistics, data quality tests, classical assumption tests, hypothesis tests with multiple linear regression methods, namely t-tests, and determination tests. The results of the questionnaire were processed with the help of SPSS. The test results show that the suitability of compensation and organizational culture do not affect the misuse of village funds. While the accounting and control systems have a negative effect on the misuse of village funds. And accounting competence has a positive effect on the misuse of village funds.